IMPLEMENTASI PERTANGGUNG JAWABAN PELAKU TINDAK PIDANA KORUPSI DALAM PENYALAH GUNAAN ANGGARAN PENDAHULUAN DAN BELANJA KAMPUNG (APBK) YANG DILAKUKAN OLEH OKNUM MANTAN KEPALA KAMPUNG MENANGA JAYA (STUDI KASUS NOMOR:13/PID.SUS-TPK/2020/PN.TJK) - alfarizzy, alfarrizy; Hartono , Bambang; Hasan , Zainudin (IBLAM LAW REVIEW, 2021)
The term corruption comes from the Latin "corruption"(English) and "corruptive"(Dutch), the literal meaning of which refers to corrupt, rotten, dishonest actions related to finances. Tanjung Karang District Court NUMBER: 13/PID.SUS-TPK/2020/PN.TJK) with the defendant Wahid Maulana who committed a criminal act of corruption, misuse of the income budget and the village Dutch in the village of Wina Jaya. The research method used in this thesis research is normative juridical approach and empirical approach. Data collection is based on library research and field studies. The factors causing the corruption crime in the aquo case are the lack of exemplary leadership, the absence of the right organizational culture, the inadequacy of the correct accountability system, the weakness of the management control system, and weak supervision. The criminal liability of the perpetrator is carried out by convicting the defendant with imprisonment for 5 years and a fine of Rp.200,000,000,- provided that if the fine isn’t paid by the defendant, it’s replaced with imprisonment for 3 months. In addition, the defendant was also sentenced to pay compensation for state financial losses amounting to Rp.457,622,500. As a form of accountability and the arena meets the elements of error and intentional in committing a crime.